Complex Valued b-Metric Spaces and Common Fixed Point Theorems under Rational Contractions. (27th June 2016) - Dubey, Anil Kumar
Abstract : The aim of this paper is to prove the existence and uniqueness of a common fixed point for a pair of mappings satisfying certain rational contraction conditions in complex valuedb -metric space. The obtained results generalize and extend some of the well-known results in the literature.